Implementasi Pendidikan Kewarganegaraan Dikalangan Pelajar dengan Menanamkan Nilai-Nilai Pancasila - Noreza, Josy; Ania, Puput; Ezalia, Nabila Tri; Luistari, Dwita (IJOCE: Indonesia Journal of Civic Education, 2022)
This study aims to determine whether applying the snowball-throwing learning model can complete the learning outcomes of students in grade V of SD Negeri 23 Lubuklinggau. This type of research is quantitative with a quasi-experimental method. Based on the results of the study showed that the average pre-test score was 44.00. After the Snowball Throwing learning model was applied to the material of community harmony and the benefits of unity and oneness in PKN lessons, the post-test results showed an average score of 85.35 and the number of completions reached 85%. If the hypothesis Zcount> Ztable (5.97> 1.64) with a confidence level of α = 0.05 which means Ho is rejected and Ha is accepted, then the average value of the learning outcomes of students in grade V of SD Negeri 23 Lubuklinggau after the Snowball Throwing learning model was applied significantly completed.   Keywords: Learning Outcomes, Elementary School, Snowball Throwing